Review: Experimental models for Barrett's esophagus and esophageal adenocarcinoma - Garman, Katherine S. (Am J Physiol Gastrointest Liver Physiol, 2012)
Several different cell culture systems and laboratory animal models have been used over the years to study Barrett's esophagus (BE) and esophageal adenocarcinoma (EAC). Most of the existing models have key differences with the human esophagus and complex pathogenesis of disease. None of the models offers an ideal system for the complex study of environmental exposure, genetic risk, and prevention strategies. In fact, different model systems may be required to answer different specific research questions about the pathogenesis of BE and EAC. Given the high mortality associated with EAC and the fact that current screening strategies miss most cases of EAC, advances in basic and translational science related to esophageal injury, repair, and carcinogenesis are clearly needed. This review describes several of the existing and potential model systems for BE and EAC with their benefits and disadvantages.